Urgensi Penyusunan Dokumen Perencanaan dalam Satuan Pendidikan Islam - Riskika Velania Istiqomah; Riza Nur Khikmiah; Mardiyah (La-Tahzan: Jurnal Pendidikan Islam, 2025)
This article discusses the urgency of preparing planning documents in Islamic education units. Islamic education, as a comprehensive system, aims to equip individuals with a solid moral and spiritual foundation. However, Islamic education faces the challenges of globalization, technological advances and social changes that require adaptation to remain relevant. Systematic planning is an important solution to ensure the effectiveness and efficiency of implementing Islamic education. This research uses library research methods in the form of media from the internet, journals, or a combination of various types of library sources that are relevant to the topic discussed. This article aims to examine in more depth the importance of preparing planning documents in Islamic education units. This article also discusses various types of planning documents commonly used in education, such as Work Plans (Renja), Budget and Cost Plans (RAB), and Strategic Plans (Renstra), as well as their effective implementation to achieve educational goals. The research method used is literature study by examining various sources such as journals and books. The results of the study show that planning has a significant role in Islamic education. Planning serves as direction, work standards, a unifying framework, and helps predict opportunities and challenges. Preparing good planning documents will speed up the performance of educational institutions, direct them to the right goals, and improve the quality and relevance of Islamic education in the future. This article provides a comprehensive understanding and practical guidance for stakeholders in improving the quality of Islamic education.